Analisis Hukum terhadap Netralitas Presiden dalam Pemilu sebagai Wujud Kepatuhan terhadap Prinsip Demokrasi - Rahayu, Dian Anggi; Santika, Syahira Rafah; Lestari, Widya Tri; Marsal, Irsyaf (Media Hukum Indonesia (MHI), 2025)
General elections are the main pillar of democracy that guarantees the political participation of every citizen, including the President. However, in the context of the 2024 elections, President Joko Widodo's statement claiming the right to campaign and take sides has caused public polemics. This is considered contrary to the principle of neutrality stipulated in Law Number 7 of 2017 and has the potential to disrupt election integrity, especially when the President uses state facilities in campaign activities. This study uses a normative juridical method with a statutory and conceptual approach to analyze the effectiveness of the application of the principle of Presidential neutrality and the role of election supervisory institutions. The results of the study show that individual integrity determines the effectiveness of neutrality in elections. When the President does not show a neutral attitude, public trust in democracy and electoral institutions decreases. Therefore, supervision by Bawaslu, KPU, and DKPP, as well as the enforcement of the code of ethics are important in ensuring the neutrality of public officials in order to maintain justice, honesty, and legitimacy in the electoral democratic process.